Swamplandia! - Russell, Karen, 1981- (Alfred A. Knopf, 2011)
Twelve year old Ava must travel into the Underworld part of the swamp in order to save her family's dynasty of Bigtree alligator wresting. This novel takes us to the swamps of the Florida Everglades, and introduces us to Ava Bigtree, an unforgettable young heroine. The Bigtree alligator wrestling dynasty is in decline, and Swamplandia!, their island home and gator wrestling theme park, formerly no. 1 in the region, is swiftly being encroached upon by a fearsome and sophisticated competitor called the World of Darkness. Ava's mother, the park's indomitable headliner, has just died; her sister, Ossie, has fallen in love with a spooky character known as the Dredgeman, who may or may not be an actual ghost; and her brilliant big brother, Kiwi, who dreams of becoming a scholar, has just defected to the World of Darkness in a last ditch effort to keep their family business from going under. Ava's father, affectionately known as Chief Bigtree, is AWOL; and that leaves Ava, a resourceful but terrified thirteen, to manage ninety eight gators as well as her own grief. Against a backdrop of hauntingly fecund plant life animated by ancient lizards and lawless hungers, the author has written a novel about a family's struggle to stay afloat in a world that is inexorably sinking.